Compact Optical Nerve Cuff Electrode for Simultaneous Neural Activity Monitoring and Optogenetic Stimulation of Peripheral Nerves - Kang-Il Song; Sunghee Estelle Park; Seul Lee; Hyungmin Kim; Soo Hyun Lee; Inchan Youn (Scientific Reports, 2018)
Abstract Optogenetic stimulation of the peripheral nervous system is a novel approach to motor control, somatosensory transduction, and pain processing. Various optical stimulation tools have been developed for optogenetic stimulation using optical fibers and light-emitting diodes positioned on the peripheral nerve. However, these tools require additional sensors to monitor the limb or muscle status. We present herein a novel optical nerve cuff electrode that uses a single cuff electrode to conduct to simultaneously monitor neural activity and optogenetic stimulation of the peripheral nerve. The proposed optical nerve cuff electrode is designed with a polydimethylsiloxane substrate, on which electrodes can be positioned to record neural activity. We confirm that the illumination intensity and the electrical properties of the optical nerve cuff electrode are suitable for optical stimulation with simultaneous neural activity monitoring in Thy1::ChR2 transgenic mice. With the proposed electrode, the limb status is monitored with continuous streaming signals during the optical stimulation of anesthetized and moving animals. In conclusion, this optical nerve cuff electrode provides a new optical modulation tool for peripheral nervous system studies.